O problema da dominação na filosofia da práxis de Antonio Gramsci - Agostinho, Thiago Lira Alves (2017)
This work has for purpose to investigate a possible justification for the problem of domination from the thought of Antonio Gramsci. Gramsci’s legacy is recognized in Western thinking by addressing the problem of domination dedicating special attention to politics in its construct, explaining how domination occurs through the hegemony in complex societies. While critical of capitalism and fascism, the author proposes to outline an alternative to counterhegemony through of a study of the modern State and the possibilities of a “revolution of the underlings”. The present work analyzes the State according to the optics of how power exerts itself from a transcendent viewpoint to modernity, in the tradition inaugurated by Machiavelli that became recognized as “political realism”. With the bourgeois revolution, the State defines itself according to the parameters of the representation and of universal suffrage, which implies the appearance of the concept of citizenship. The philosophy that gives the foundation of this conception is the natural law contractualist. The natural law enters into crisis with Hegel and is replaced by historicism, which meets in Marx and marxism one of its greatest interpreters. Gramsci is inserted in this tradition, so it’s addressed some authors such as Machiavelli, Marx, and Lenin – whose historical significance is paramount to gramscian thought. The project of a communist revolution in Gramsci includes understanding the relationships of capitalist domination in the light of a triumphant revolution at the time, that is, the model of insurgency occurring in Russia in 1917. The differential is that the West does not meet the same “conditions of possibility” as in that country, and this reading features Gramsci has marxist thinker at the same time orthodox and unorthodox. In this project, in order to achieve a successful revolution given to the greater complexity of Western societies, the involvement of several sectors of civil society, from intellectuals to political parties, with a view to conquering ideological hegemony, a key point in order to bring down the bourgeois State in all its ramifications. The concept of revolution, for Gramsci, is not the mere reduction of pure and simple armed violence, but it is conjunction with a radical intellectual and moral reform of society. It is necessary to underline that Gramsci’s writings do not have a fineshed definition of the concept of “domination”: his grandiose scope was published in both his juvenile writings – a militant who acted in the Communist Party of Italy – until his incarceration and the adverse intellectual production of the Prison Notebooks, in which he found his great theoretical contribution in fact.